Widening the European Union : the politics of institutional change and reform - Steunenberg, Bernard (Routledge advances in European politics, 2003)
Containing contributions from a distinguished team of European academics, this book focuses on those institutional reforms of the European Union that may be necessary to make the enlargement possible.